PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR : GUNA MENINGKATKAN MINAT BACA PADA ANAK USIA DINI (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
Indonesian language learning at the elementary school level plays a crucial role in developing students' communication skills from an early age. The main focus of this learning is to introduce and improve language skills through four main components: listening, speaking, reading, and writing. Indonesian language learning in elementary schools is adapted to the cognitive and social development stages of students, with the application of interesting and innovative methods, such as games, stories, and group discussions. In addition to improving language skills, this learning also aims to shape students' character, critical thinking skills, and social skills. Furthermore, Indonesian language learning also supports the introduction of Indonesian cultural values and increases understanding of the importance of language as an effective communication tool in everyday life. With the right approach, Indonesian language learning can be a strong foundation for students' academic and social success in the future.